Pengaruh Pengungkapan Lingkungan, Sosial, dan Tatakelola (ESG) dan Green Accounting terhadap Nilai Perusahaan - Chelsea Diva Antonetta; Febryanti Simon (Politeknik Ganesha Medan, 2026)
Sustainability aspects are increasingly emphasized in modern business practices, including among companies listed on the Indonesia Stock Exchange. This development has been well supported by the launch of the ESG Leaders Index, which consists of 30 companies with strong sustainability performance. The implementation of Environmental, Social, and Governance (ESG) practices and green accounting not only serves as compliance with regulatory requirements but also acts as a signal to investors regarding a company’s commitment to sustainability. This study aims to analyze the influence of ESG Disclosure (Environmental, Social, and Governance), as well as green accounting, on firm value among companies included in the ESG Leaders Index for the 2022–2024 period. A quantitative approach is employed using panel data regression with the Fixed Effect Model with GLS cross-section transformation. The results reveal that environmental disclosure has a significant negative effect on firm value, social disclosure has a significant positive effect on firm value, governance disclosure has a significant positive effect on firm value, and green accounting shows no significant effect on firm value. These findings indicate that investors have begun to incorporate sustainability aspects as an important consideration when making investment decisions.